Support Process of Surgical Block: Patient safety strategies - Rosa Martos Moreno; Inmaculada Alonso Gutiérrez; Concepción González García; Mª Jesús Martín González; Alfredo Castro Díaz; Guadalupe Pareja Toré (Fundación para el Desarrollo de la Enfermería, 2010)
Second edition of Guide of designe and continues improvement of the Care Integrated Procedures identifies us indispensable elements, among others, the ones related with the dimension patient safety. Objetive of this work has been the elaboration of a Surgical patient path document which contains those elements. The result has been a document in the shape of a indivisible triptych, continent of a lot of safety barrier ( pre surgical and assist surgical check-lists, clinic guides, etc) that should avoid the appearance of adverse events. For its suitable employment it would be necessary introducing the document before the movement of the patient to the Surgical Block, during the pre surgical preparation at the Hospitalization Unit. It would be moved forward a step at the third level of the Process Architecture, to guarantee the Cares continuity and the Safety.